An experimental study on the determination of a hermetic reciprocating compressor's discharge and suction losses - Bacak, Aykut; Pinarbasi, Ali; Dalkilic, Ahmet Selim (SAGE PUBLICATIONS LTD, 2024)
The most popular approach to determine compressor losses is to generate compressor pressure-volume indication diagrams. The pressure-volume indication diagram of a novel hermetic reciprocating compressor for household refrigerators operating with R600a was experimentally obtained under American Society of Heating, Refrigerating and Air-Conditioning Engineers (54.4 degrees C/-23.3 degrees C) and additional specific working conditions of (40 degrees C/-25 degrees C), (25 degrees C/-20 degrees C) and (35 degrees C/-15 degrees C). Apart from most studies, experiments have been performed using a calorimeter. The alteration of suction and discharge pressures with crank angle of the investigated compressor was presented as both graphical and numerical information during condensation and evaporation, separately. As a result of the analyses, total compressor losses increased with decreasing the condensation pressure. These losses were 10%, 8.7%, 5.7% and 4.6% of the total work and they were observed at the same speed of 1300 rotation per minute (rpm) as the lowest one under all operating conditions. Besides, the suction line losses having the largest losses in the compressor were calculated as 50.1%, 50.9%, 64.9% and 67.9% of the total one, and it has been determined that they increased with increasing the condensation pressure. Due to the more complex design of the equipment in the suction line, the losses in this region were found to be higher than those in the discharge line, as expected.
Keywords: Hermetic reciprocating compressor; pV indicator diagram; discharge losses; suction losses; OPTIMIZATION; VALVE; Engineering